DOMESTIC LABOR MARKET CONDITIONS AS THE BASIS FOR THE USE OF FOREIGN WORKERS FOR ENTREPRENEURS IN INDONESIA - Wibawa Putra, Komang Satria; Prasada, Dewa Krisna; Kurniawan, I Gede Agus; Astawa, I Nengah Dasi (Kertha Semaya : Journal Ilmu Hukum; Vol 13 No 7 (2025)DO - 10.24843/KS.2025.v13.i07.p14, 2025)
Penelitian ini bertujuan untuk tata cara penggunaan tenaga kerja asing berdasarkan hukum positif Indonesia serta kondisi pasar tenaga kerja dalam negeri sebagai dasar penggunaan tenaga kerja asing di Indonesia. Penelitian ini menggunakan metode peneltian normatif dengan pendekatan perundang-undangan dan analisis konseptual. Hasil penelitian menunjukkan bahwa prosedur penggunaan tenaga kerja asing di Indonesia diatur secara komprehensif dalam berbagai peraturan perundang-undangan di khususnya pada Peraturan Pemerintah Nomor 34 Tahun 2021 tentang Penggunaan Tenaga Kerja Asing dan Peraturan Menteri Ketenagakerjaan Nomor 8 Tahun 2021 tentang Peraturan Pelaksanaan Peraturan Pemerintah Nomor 34 Tahun 2021 Tentang Penggunaan Tenaga Kerja Asing. Setiap pengusaha yang akan mempekerjakan tenaga kerja asing wajib menyusun rencana penggunaan tenaga kerja asing yang secara otomatis dalam penyusunannya telah memperhatikan kondisi pasar kerja dalam negeri. Akibat hukum bagi pengusaha yang mempekerjakan tenaga kerja asing tanpa rencana penggunaan tenaga kerja asing sesuai dengan ketentuan yang berlaku dapat dikenakan sanksi administratif. ABSTRACT This research aims to examine the procedures for the use of foreign workers based on Indonesia's positive laws and domestic labor market conditions as the basis for the use of foreign labor in Indonesia. This research uses normative research methods with a legislative approach and conceptual analysis. The results of the study show that the procedures for the use of foreign workers in Indonesia are comprehensively regulated in various laws and regulations, especially in Government Regulation Number 34 of 2021 concerning the Use of Foreign Workers and Regulation of the Minister of Manpower Number 8 of 2021 concerning Implementation Regulations of Government Regulation Number 34 of 2021 concerning the Use of Foreign Workers. Every entrepreneur who will hire foreign workers is required to prepare a plan for the use of foreign workers which automatically in its preparation has paid attention to the conditions of the domestic labor market. Legal consequences for employers who hire foreign workers without a plan to use foreign workers in accordance with applicable provisions may be subject to administrative sanctions.